“You can always hold out a piece of bread in the void” : Food and Duras’s War of Waiting - Katherine Roseau; Arely Cuevas-Flores (Studies in 20th & 21st Century Literature, 2026)
This article suggests that “La Douleur” is a text of the embodied pain of separation from a loved one, which manifests in self-deprivation of food. The text depicts a collective experience (Duras represents millions of women) that is at the same time deeply isolating: waiting for a loved one to return from war. This article draws on the psychology of grief and missingness to study Duras’s autobiographical protagonist, Marguerite, and her obsession with food during her husband’s absence and then recovery. To cope with the unknown about Robert L., Marguerite continues a bond with him. She brings him into her own body, making room for him by way of her own hunger. Then, after Robert L.’s return, she intimately beholds the sacredness of humanity as it is threatened by the violence of starvation. This article moves the discussion on this text beyond the focus on the “unspeakable.” It highlights the period of waiting which was intensified by a sudden flood of photographs that revealed the horror of Nazi camps. While it is well established that Duras writes of the void throughout her oeuvre, this article underscores a different type of void, one created by food and an interplay of absence and presence.
Keywords: Marguerite Duras; void; war writing; food; concentration camp